Basics of Diagnosing Congenital Hydronephrosis in Children - Zokirjon o’g’li, Shukrulloyev Fayozjon (Journal of Science in Medicine and Life, 2024)
Congenital obstruction of the ureteropelvic junction (UPJ) and hydronephrotic transformation are well-known conditions to clinicians. Diagnosis, examination algorithms, and successful surgical treatments have been repeatedly described in articles and pediatric surgery manuals. However, with the introduction of ultrasound into routine perinatal practice in the 1980s, as well as the use of modern radionuclide and imaging techniques and minimally invasive surgical correction methods, our understanding of hydronephrosis has significantly changed in several aspects.